1991
DOI: 10.1152/ajplung.1991.261.2.l156
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic contractile response of pulmonary artery to hypoxia

Abstract: Isolated perfused lungs exposed to low O2 exhibit a hypoxic pulmonary vasoconstriction response that is transient in nature. The purpose of this study was to determine whether the isolated pulmonary artery behaves similarly in response to hypoxia. Rat pulmonary arterial rings were placed in tissue baths (37 degrees C, air-5% CO2, pH = 7.4) and attached to force transducers. Maximum contractile responses (Po) to high K+ were elicited. After washout, arterial rings were submaximally contracted and made hypoxic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 0 publications
7
56
1
Order By: Relevance
“…We and others (3,10,28) have reported that in isolated rat PA, a biphasic pattern of contraction occurs in response to acute hypoxia. The role of PKC on HPV in isolated perfused lung has been demonstrated in previous studies (1,32); however, the involvement of PKC in the isolated PA is less clear.…”
Section: Discussionmentioning
confidence: 72%
“…We and others (3,10,28) have reported that in isolated rat PA, a biphasic pattern of contraction occurs in response to acute hypoxia. The role of PKC on HPV in isolated perfused lung has been demonstrated in previous studies (1,32); however, the involvement of PKC in the isolated PA is less clear.…”
Section: Discussionmentioning
confidence: 72%
“…However, the response of the pulmonary artery to alveolar hypoxia is complex with vasorelaxation and vasoconstriction appearing at different stages and in different parts of the arterial arborization (Madden et al 1985;Bonnet, Argibay & Garnier, 1989;Bennie, Packer, Powell, Jin & Rhoades, 1991). In this report we show that severe hypoxia relaxes large diameter pulmonary arteries (PAs) of the rabbit and enhances rather than inhibits a K+ current in smooth muscle cells isolated from this tissue.…”
Section: Introductionmentioning
confidence: 74%
“…Hence, pulmonary arteries constrict biphasically when exposed to hypoxia (450 Torr). An initial transient constriction (phase 1) is followed by a slowly developing and sustained increase in tone (Albarwani et al, 1994;Bennie et al, 1991;Jin et al, 1992;Kovitz et al, 1993;Robertson et al, 1995), (phase 2). Phase 1 occurs independently of the endothelium and is thought to result from depolarization of the smooth muscle cell membrane (Evans et al, 1996;Osipenko et al, 1997;Yuan et al, 1993;Post et al, 1992) and Ca 2+ in¯ux through voltagegated Ca 2+ channels (Harder et al, 1985;McMurty et al, 1976;Madden et al, 1992;Corn®eld et al, 1993;Salvatera & Goldman, 1993;Vadula et al, 1993).…”
Section: Introductionmentioning
confidence: 99%